Implementing of Machinery Distribution Program on Sustainable Agriculture and Rural Development: Basis for Action Plan - Rivera, Deo; Flores , Joy (Journal of Interdisciplinary Perspectives, 2024)
This study utilized a descriptive correlation research design to assess the level of implementation of the Machinery Distribution Program by the Department of Agriculture Regional Field Office I (DA RFO I) in La Union. It also investigated the challenges encountered during the program's implementation. The respondents included LGU municipal agriculturists, banner program coordinators, and the Chairman/President of the Farmer Cooperative Association, with a total of 60 participants. Data were collected using a researcher-made survey questionnaire and analyzed using frequency counts, percentages, weighted means, and Pearson correlation. The analysis indicated that most beneficiary associations are well-established, operating for over a decade with more than 100 members, typically in lowland areas, and properly registered with government agencies. The program was found to be fully implemented. However, there was no significant relationship between the profile variables and the program's implementation level. Several challenges were identified, including limited farm sizes, inappropriate or missing equipment, uneven allocation favoring certain associations, inaccessible roads for machinery delivery, and a mismatch between provided machines and the layout of farmlands. The study concluded that while the program was fully implemented, addressing these challenges could improve farming conditions for the farmers and associations. An Action Plan was recommended to address the identified problems in the Machinery Distribution Program's implementation.